2017
DOI: 10.1590/1678-77572016-0313
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of human papillomavirus (HPV) in oral mucosal lesions of patients at the Ambulatory of Oral Diagnosis of the Federal University of Sergipe, Northeastern Brazil

Abstract: The role of human papillomavirus (HPV) in oral carcinogenesis is still controversial as detection rates of the virus in oral cavity reported in the literature varies greatly. Objective The aim of this study was to evaluate the frequency of HPV infection and its genotypes in patients with oral lesions at the Ambulatory of Oral Diagnosis of the Federal University of Sergipe, Brazil.Material and Methods We conducted a molecular study with 21 patients (15 females) aged from two to 83 years with clinically detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A lower but significantly different prevalence of oral HPV in oral lesions was found among Croatian individuals (17%) and Chilean patients (11%) with oral cancer [22,23]. However, in a Brazilian study, it was found the highest prevalence of oral lesions from South America (81%) [24].…”
Section: Discussionmentioning
confidence: 88%
“…A lower but significantly different prevalence of oral HPV in oral lesions was found among Croatian individuals (17%) and Chilean patients (11%) with oral cancer [22,23]. However, in a Brazilian study, it was found the highest prevalence of oral lesions from South America (81%) [24].…”
Section: Discussionmentioning
confidence: 88%
“…However, in the case of the third pathogen investigated here, the human papillomavirus (HPV), no systematic association has been established[ 6 , 22 - 24 ]. While the oncogenic properties of HPV have been demonstrated in studies of other portions of the digestive tract[ 25 - 28 ], its possible relationship with GC is still unclear[ 23 , 24 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is probably associated to the fact that from the more than 170 genotypes described, we used in this study only a limited number of probes, and it is unknown with certainty what percentage of the genome is common for those genotypes not commercially available. High discrepancies are found when using methods such as ISH or PCR, as the latter possess a higher sensitivity but lower specificity, and studies using PCR shows higher percentages of positivity (19). In conclusion, low-risk HPV 6/11 are the most common subtypes found in the oral cavity, even though, a small percentage of hyperplastic papillary lesions are associated with HPV, they comprise a wide group of lesions that deserves further studies to better clarify its classification and etiology.…”
Section: Discussionmentioning
confidence: 99%